IMPACT OF COMMUNITY INITIATIVES ON NON-EMS BYSTANDER CPR RATES - MAMA, DR.MISHI MAMA; P. RATO; M. BABA; PORF.DHANJI (International Journal of Multidisciplinary Research and Studies, 2021)
Bystander CPR rates have steadily increased in England between 2014 and 2018. In West Yorkshire, there are two important developments during now. We aimed to explain whether postcode districts (PCDs) with more cumulative annual ‘Restart a Heart’ (RSAH) and/or Community First Responder (CFR) scheme activity between 2014 and 2018 were related to greater improvements in non-EMS bystander CPR rates for out-of-hospital cardiopulmonary arrest (OHCA) in comparison with PCDs within the same region with lesser or no such historic activity during the identical fundamental measure. METHOD We collated data from the OHCA Outcomes Registry for all non-EMS witnessed OHCA in West Yorkshire treated by Yorkshire Ambulance Service. We analyzed clusters of PCDs with high and low levels of RSAH and CFR activity between 2014 and 2018 using descriptive statistics, and comparisons were made between groups using chi-square and t-test. RESULTS The reported bystander CPR rate for non-EMS witnessed OHCA cases for West Yorkshire rose from 38.4% in 2014 to 69.7% in 2018. the biggest increases were seen in PCDs with high RSAH activity (+34.3%) and within the combination of high RSAH and low CFR activity (+38.5%). There was no significant difference when considering the interaction between RSAH and CFR groups. CONCLUSION The data infer the likelihood of a non-significant association between improved non-EMS bystander CPR rates and RSAH training and CFR scheme activity. We recommend coordinated mass training, specifically for youngsters in regions where CPR isn’t a compulsory part of the varsity curriculum.